Fooling the mind: An approach on attention and concentration based on deceptions - Rafael G. Lenzi (Actes Sémiotiques)
This article explores attention and concentration in relation to the human senses, as depicted in The official C.I.A. Manual of Trickery and Deception (2009). The manual teaches field agents tricks, based on those used by magicians, for espionage purposes, such as object manipulation and covert communication. Its methodology focuses on guiding attention to specific points, providing insights into manipulating perception and awareness. The deception presented by the film Argo (2012) is referenced to illustrate practical applications. The study distinguishes between attention and concentration as different expressions of perception, based on Merleau-Ponty’s approach, and examines the deceptive structures and their functioning through narrative semiotics. Additionally, Gibson’s theory of affordances is contemplated to understand how spies’ interpretation of the environment influences their effectiveness. The results indicate that attention can be handled as an umbrella for somatic senses, being able to be detached from them and from the victim as a whole.